Effectiveness of Mindfulness Therapy to Reduce Depression Levels in Female Prisoners - Nurhikmah, Siti; Diah Suslianingrum, Elfa; Dewita, Sisri (Lafadz Jaya Publisher, 2024)
This research is a quantitative research using a one group pretest-posttest design experimental method with the aim of the research to determine the effectiveness of mindfulness therapy in reducing levels of depression in female prisoners. Subject selection was carried out by purposive sampling. The subjects involved were five female prisoners who had the BDI-II category of moderate depression with a minimum sentence of less than one year in prison. The level of depression was measured using the BDI-II (Beck Depression Inventory) scale by Beck (1976). The BDI-II scale was given before and after being given mindfulness therapy and the data collected was analyzed using a paired sample t-test and effectiveness test. The results of the study showed that there was a significant difference in the level of depression, where the average level of depression decreased after receiving the intervention, the level of depression in subjects who previously had an average score of 25.4 decreased to 17.6. This shows that the intervention provided in the form of mindfulness therapy can reduce the level of depression in the subject. To test whether the results of the intervention were significant or not, the researcher also carried out a significance test using paired sample t-test analysis, but first the researcher carried out a normality test on the research data. Based on the results of the Difference Test analysis, a significance value of 0.022 (p<0.05) was obtained, meaning that there was a significant difference between the pretest and posttest scores, so it could be concluded that there was a decrease in the level of depression in research subjects after being given intervention in the form of mindfulness therapy.